Why the Gore report will probably fail - Hart, David Kirkwood; Hart, David W. (1997)
The Gore Report on Reinventing Government summarizes the findings of the National Performance Review Board. It is a well-intentioned endeavor, containing many perceptive insights and solutions. Unfortunately, the NPR failed to consider a number of fundamental problems, which will probably cause the reform effort to fail. Foremost among the problems are the neglect of "the public interest," reform by command rather than by persuasion, the trivialization of the "public" service, the devaluation of citizenship and the cynicism of frustrated expectations. This article discusses some of the implications of those problems. - Reproduced
Keywords: Public administration - United States; Administrative reform - United States; Administrative reform